GEOLOGICAL-STRUCTURAL-GEOCHEMICAL FEATURES OF OIL SHALE AND HYDROCARBON DEPOSITS FORMATION OF BOLTYSH IMPACT STRUCTURE - Bahriy, I.D.; Pochtarenko, V.I.; Dubosarskyi, V.R.; Yantsevych, O.O.; Semenyuk, V.G.; Hryha, N.V; Malyshev, O.N.; Gaphych, I.P. (Institute of Geological Sciences, NAS of Ukraine, 2016)
The facilities and efficiency of complex near-surface search technologies application at studying of geological-structural-geochemical features of unconventional deposits of energy resources formation in the conditions of impact structures (for example, Boltysh structure) are considered. Conducted investigations provide an opportunity to clarify the structural-tectonic features of the studied object and to construct a set of maps which shows the distribution of temperature and gas indicators, zones and areas with various geodynamic activity and fluid permeability. In general, application of STAGR technologies enables to allocate areas prospective on hydrocarbons within impact structure.